Pengembangan Buku Pedoman Manajemen Life Skill untuk Peserta Didik di SLB Negeri 1 Lima Kaum - Wardila, Ance Oktavia (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
This research is motivated by: 1) Determination of teaching materials and material content does not fully refer to students' needs, 2) The purpose of learning skills in most schools is still a compulsory subject, 3) Schools teach the ability to market the work of ABK, 4) Teacher human resources are not yet all of them have competence in mastering the content of the material and learning methods for ABK skills. For this reason, researchers have created a guidebook for teachers. With this guidebook, it is hoped that teachers will be more creative in managing life skills education in schools. Apart from that, having a manual means that we have provided children with the provisions to enter the world of work. The purpose of this research is to produce a life skill management manual for students at SLB N 1 Lima Kaum. This type of research is R&D research with the ADDIE model which includes the stages of analysis, design, development, implementation and evaluation. This study uses data analysis techniques, namely, validation sheets and questionnaires. The validation sheet was assessed by three expert experts. Based on the results of this study, it can be stated that the validation of the life skill management handbook for SLB Negeri 1 Lima Kaum students. This product has also been validated by three validators with very valid criteria (86.29%). In the practicality stage, from the results of the questionnaire, the responses of SLB Negeri 1 Lima Kaum teachers obtained a percentage (90.83%) with very practical criteria. Thus the life skill management handbook for SLB Negeri 1 Lima Kaum students has become a reference guide in implementing life skill management.